PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN AUDIO VISUAL TERHADAP HASIL BELAJAR PADA PEMBELAJARAN PKN SISWA KELAS VB SDN SUNGGUMINASA V - Suardi; Musdalifah Syahrir, Nur Khalis.T (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the effect of using audio-visual learning media on the learning outcomes of Civics Education (Pancasila Education) among fifth-grade students at SDN Sungguminasa V. The research problem is: "Is there an effect of using audio-visual learning media on the Civics Education learning outcomes of fifth- grade students at SDN Sungguminasa V?" This study employed a quantitative method with a quasi-experimental approach. The sample consisted of 29 students, including 12 boys and 17 girls. Data collection techniques included observation of student learning activities, pretests, and posttests. Inferential statistical analysis was conducted using a paired sample t-test with the help of SPSS version 26. The results showed that the use of audio-visual learning media had a positive effect on student learning activities, increasing from 45.4% in the first session to 84.1% in the third session. Student learning outcomes also improved significantly, with the average pretest score rising from 60.00% to 81.75% in the posttest, a gain of 21.75 points. However, the paired sample t-test analysis showed a significance value (Sig. 2- tailed) of 0.220 (p > 0.05), indicating that the improvement was not statistically significant. Nevertheless, the use of audio-visual media practically enhanced student engagement and learning outcomes. This finding aligns with previous studies indicating that audio-visual media can increase students’ interest, attention, and comprehension. Therefore, audio-visual learning media are worth further development in the teaching of Civics Education at the elementary school level.